A comparative legal study of power to declare emergency in Malaysia and India / Pamela Surang, Isznie Anis Ismail and Alex Seliong Jabal - Surang, Pamela; Ismail, Isznie Anis; Jabal, Alex Seliong (2009)
This research paper deals with the comparative legal study of power to declare emergency between India and Malaysia. The objective of this study is to compare the law in relation to declaration of emergency in Indian and Malaysian Constitution. Then, the comparison made will help to identify any weaknesses in the system and provide information on mechanisms that are used in both countries to control proclamation of emergency. Besides that, some research that will be made is important to identify any law or regulation that was enacted during the state of emergency. The effects of these emergency ordinances to fundamental liberties will be examined and clarified. In order to make the research becomes more accurate, two interviews will be conducted and the information from it will be compiled so that we can see different opinions and recommendations about the subject matter. The conclusion will be made based on which system of controlling the power to declare emergency is more effective. Recommendations would also be given so that the government could use it as a guideline to overcome the problems arises.